2020
DOI: 10.1108/caer-06-2020-0128
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the poverty alleviation relocation program on diet quality among low-income households

Abstract: PurposeThis paper aims to examine impacts of the poverty alleviation relocation (PAR) program on diet quality of low-income households in China. We explore the impact mechanism of relocation on diet quality and the heterogeneous effects of different relocation modes.Design/methodology/approachA fixed effects model is constructed using panel data of 1126 low-income households collected over three years in eight provinces of China. The PAR program provides a natural experiment which dramatically changes the livi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 37 publications
1
11
0
2
Order By: Relevance
“…The finding that diet diversity improves with increasing level of income is consistent with the theoretical assumptions on consumer behavior previously formulated by Dorce et al [ 152 ], Panait et al [ 153 ], Chandra et al [ 154 ], and Qiu et al [ 43 ]. People who feel increasingly food secure due to a higher purchasing power are more certain about their ability to obtain higher-quality and more nutritious foods.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The finding that diet diversity improves with increasing level of income is consistent with the theoretical assumptions on consumer behavior previously formulated by Dorce et al [ 152 ], Panait et al [ 153 ], Chandra et al [ 154 ], and Qiu et al [ 43 ]. People who feel increasingly food secure due to a higher purchasing power are more certain about their ability to obtain higher-quality and more nutritious foods.…”
Section: Discussionsupporting
confidence: 89%
“…Wu et al [ 40 ], Arce et al [ 5 ], and Ranjit et al [ 29 ] found economic factors to influence the intake of value-added nutrient-rich products, but such an effect could be expected. What is more striking is the dependence of staple intake on the level of income revealed by Sarica et al [ 41 ], Sikandar et al [ 42 ], and Qiu et al [ 43 ].…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…The poverty incidence rate of many resettlement sites is still high, so the follow-up development of the resettled population is a crucial issue. The relevant research results can be classified into two categories: one is a comprehensive study of the poverty alleviation effect and subsequent development of the resettled population [38,39]. For example, using panel data and fixed effects models, Leng et al explored the impact of PAR on household income.…”
Section: Follow-up Development Of Resettled Populationmentioning
confidence: 99%
“…魏旭红 等:易地扶贫搬迁对山区农户福祉的影响 框架构建 [9][10][11] 、福祉水平评价 [12][13][14] 及其影响因素分析 [15,16] 等方面,形成了人类发展指数 [17] 、MA 福祉框架 [18] 、可行能力理论 [19] 、人类需求理论 [20] 等评估框架。易地扶贫搬迁作为一项改善贫困 地区农户生活条件的政策措施,也是增进农户福祉的主要推手 [21] 。研究发现,搬迁不仅能够 提高农户的总收入,还会对农业收入、工资性收入产生显著的正向影响,并且搬迁后随着收 入水平的提高,低收入家庭的膳食质量也逐渐得到改善 [22,23] 。同时,易地扶贫搬迁还会打破农 户原有的社会关系网络,使其社会融入遭受阻碍 [2,24] 。宁静等 [5] 还发现易地扶贫搬迁通过改善 农户的生产生活条件,使得农户能够积累足够的生计资本,进一步改善了农户的生计资本结 构。研究也发现,搬迁后住房、教育、医疗、交通等方面的改善能够提升搬迁户的生活满意 度,而在搬迁过程中农户对政策信息获取较少、其就业向非农化突变会拉低农户的生活满意 度 [4] 。另外,搬迁后较好的基础设施、公共服务、社会交往、经济状况和居住环境更有利于农 户幸福感的提升以及与迁入地情感纽带的建立 [25][26][27] 。 总体来看,在研究内容上,已有研究多从农户的收入或生活满意度等单一维度出发 分析易地扶贫搬迁对农户的影响。实际上,福祉包括主观福祉与客观福祉,前者侧重于 个体对自身生活水平的主观认知和情感表达 [28] ,后者则侧重于在考虑生活条件、经济水 平和社会关系等因素的情况下衡量个体或社会的福利水平 [29] ,单一维度的考察难以全面 综合反映易地扶贫搬迁对农户福祉的影响;在研究方法上,目前研究多采用倾向得分匹 配法、固定效应模型等方法 [3,5,22,23] ,通过对政策实施前后搬迁户与非搬迁户之间差异的比 较,以分析易地扶贫搬迁政策的效果,鲜有研究去探究易地扶贫搬迁对搬迁前后农户福 祉变化的影响;在研究区选择上,当前研究较少去关注整乡搬迁区农户的福祉变化。因 此,有必要将主观福祉与客观福祉结合起来分析易地扶贫搬迁对整乡搬迁区农户福祉变 化的影响,以便更好地了解易地扶贫搬迁政策的综合效果。 山区是能源、矿产资源的富集区,也是高度依赖自然资源谋生的人群集中区,全球 约有 12% 的人口居住在山区,其中超过 40% 的人口分布在发展中国家 [30] 。中国是一个山 地大国,山区面积约占国土面积的 2/3,人口约占全国的 56% [30] ,受自然地理属性的限 制,山区经济社会发展水平普遍较低 [31] 。地处西秦岭的陇南山区不仅是典型的自然灾害 易发多发区,也是甘肃乃至全国脱贫攻坚的主战场之一,还是全国易地扶贫搬迁典型区 域 [32] 。鉴于此,本文基于陇南山区坪垭藏族乡易地扶贫搬迁农户的调查数据,在构建农 户福祉评价指标体系、利用熵值法评估搬迁前后农户福祉变化的基础上,采用分位数回 归分析易地扶贫搬迁对农户综合福祉变化的影响,旨在为推进易地扶贫搬迁后续扶持工 作提供科学参考。 1 理论框架 易地扶贫搬迁旨在从根本上消除"一方水土养不起一方人"的本底脆弱性问题 [32] , 并且主要通过就业支持、资金支持、物质支持三种支持性政策干预来改善搬迁家庭的客 观福祉及主观福祉 [33] (图 1) 。其中,就业支持是对"人力"的支持,是实现易地扶贫搬 迁"稳得住"的关键因素。人力资本理论指出,人力资本的匮乏是导致相对贫困地区农 户收入提升缓慢的重要因素之一 [34]…”
unclassified
“…是增加经济收入和提升家庭福祉 [22] 。易地扶贫搬迁主要通过提供资金补贴、贴息贷款 等,来补贴搬迁户在生活用品及耐用消费品等方面的消费。其中,资金补贴不仅能够激 发农户提高受教育水平的动力和能力,也能提高农户在饮食、社会关系等方面的支出 [37] , 从而有效改善农户的生活质量;贴息贷款不仅能够提高农户的借贷能力并保障农户的经 济安全,也能提升农户抵御生计冲击的能力。物质支持是对"物力"的支持,是易地扶 贫搬迁农户重构发展空间的重要手段。在搬迁前,由于多数群众所处区域位置偏远、基 础设施条件落后以及公共服务供给不足,时常面临着教育、医疗、养老和就业等方面机 会不公平的问题,无疑对其可持续发展能力构成限制 [38] 。搬迁之后,农户集中居住在川 坝河谷区,铁路、高速公路穿乡而过,交通便捷度大幅提升,污水管网、电力电信等基 础服务设施齐全,学校、医院等公共服务设施完善 [3] [8] 。它 既涉及财富、教育、健康、安全、设施等物质社会属性,也体现个人对于目前生活总体 质量的认知和情感 [39] 。基于 《千年生态系统评估报告》 中福祉内涵及相关研究 [40,41] ,本文 从收入与基本物质需求、安全、社会关系、健康、文化适应 5 个维度刻画搬迁农户的客 观福祉 (表 1) 。其中,收入增加是农户最期望的生计结果,对改善福祉有重要作用 [22] ; 基本物质需求是农户维持生计的物质保障 [9] ;经济安全是家庭抵御金融风险的中坚力 量 [42] ,饮水安全是农户健康和生命安全的基本保障,人身安全是保障自身发展的必要条 件 [36] ;拥有良好的社会关系是农户获取技术信息的纽带,也是实现集体利益的桥梁 [6,33] ; 医疗支出占比能反映家庭成员的总体健康状况,而饮食质量则反映了农户的饮食健康状 况 [23,40] ;此外,农户在搬迁后不仅需要物质和经济上的支持,还需要适应新的环境,故用 到达最近寺院的时间、参加宗教活动的次数、参加文艺活动的次数来测度坪垭藏族乡搬 迁农户对新环境的文化适应程度 [32]…”
unclassified